1997
DOI: 10.3109/00365519709060029
|View full text |Cite
|
Sign up to set email alerts
|

Metabolic cobalamin deficiency in patients with low to low-normal plasma cobalamins

Abstract: Over a 2-year period, we examined 48 patients with P-cobalamin levels in the difficult "grey zone" at the lower reference limit detected by a competitive protein binding assay using intrinsic factor as binder. In 21 of 30 patients (70%) with low P-cobalamins we could not establish the diagnosis of metabolic cobalamin deficiency, but 1 of 18 patients (6%) with low-normal P-cobalamin values was confirmed metabolically cobalamin-deficient. Half of these 30 patients with low P-cobalamins had neuropsychiatric disor… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

0
10
0

Year Published

2000
2000
2014
2014

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 11 publications
(10 citation statements)
references
References 23 publications
0
10
0
Order By: Relevance
“…9 Their accidental coexistence with a suspected clinical finding can sometimes be misconstrued. 12 The initial task is to document the clinical and laboratory findings and prove their connection to cobalamin deficiency. Metabolic tests, such as serum methylmalonic acid (MMA) or plasma homocysteine, can be useful when the clinical picture is equivocal but are sometimes unreliable themselves.…”
Section: Pathophysiologically Based Management Of the Cobalamin-deficmentioning
confidence: 99%
“…9 Their accidental coexistence with a suspected clinical finding can sometimes be misconstrued. 12 The initial task is to document the clinical and laboratory findings and prove their connection to cobalamin deficiency. Metabolic tests, such as serum methylmalonic acid (MMA) or plasma homocysteine, can be useful when the clinical picture is equivocal but are sometimes unreliable themselves.…”
Section: Pathophysiologically Based Management Of the Cobalamin-deficmentioning
confidence: 99%
“…Only one-half or fewer of low cobalamin concentrations are explained by malabsorption of either free or food-bound cobalamin, and dietary insufficiency is uncommon even among the elderly (2)(3)(4)(5)(6). Moreover, metabolic studies indicate that 15-40% of patients with low serum cobalamin do not have cobalamin deficiency (1,2,(7)(8)(9)(10), which suggests that as many as 15-40% of cobalamin values below the reference interval may be diagnostically misleading. This diagnostic dilemma is not resolved by changing reference intervals for cobalamin because low concentrations that represent true metabolic deficiency and malabsorption are not always lower than low concentrations that do not.…”
mentioning
confidence: 99%
“…Concerning MMA, fairly extensive conclusions were drawn on the background of these non-controlled studies. The major problem occurred when several authors suggested that vitamin B-12 deficiency could be defined as an increased level of MMA that decreased after administration of vitamin B-12 [5,20,27,28]. This definition was based on the analysis under evaluation, and the usefulness of MMA had become a self-fulfilling prophecy.…”
Section: Discussionmentioning
confidence: 98%